Implementation of Multicultural PAI Values in the Islamic Religious Education Curriculum in the Merdeka Curriculum in Elementary Schools - Sari Agustiani; Sri Wahyuni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The implementation of Islamic educational values in the Islamic Religious Education curriculum in the Merdeka curriculum can be implemented by Islamic Religious Education teachers in elementary schools through their role as developers, one of which is in the development of Islamic religious education teaching modules. This development can be improved by including a content of multicultural Islamic values in teaching modules, especially in the learning objectives, student profiles, fishing perceptions and questions, learning methods and activities, assessment instruments, reflection and enrichment techniques. The values of multicultural Islamic education that can be included as content in curriculum development include: tolerance, equality, justice and democracy (freedom). The implementation of curriculum development will at least be an opening path to bring the learning process of Islamic Religious Education in an inclusive direction.